Optimasi Penilaian Mutu Kerja Pegawai Dengan Metode Clustering Pada RRI Tual - Bunga, Alex Frianco; Prasetyo, Sri Yulianto Joko (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
This research aims to optimize the process of assessing employee work quality at Radio Republik Indonesia (RRI) Tual using the clustering method. This research method involves analyzing historical data on employee performance assessments as well as applying clustering techniques to group employees based on their performance characteristics. The data used includes employee performance evaluations over the past year, including employee performance, competency, productivity and projects. The clustering method used is K-means clustering to group employees into categories according to the level of quality of their work. The results of this research indicate that the use of the clustering method can optimize the process of assessing employee work quality by allowing the identification of groups based on their performance. In this way, management can provide more appropriate and fair recognition and rewards, as well as design skills development programs that suit each group. The case study at RRI Tual indicates that implementing the clustering method can increase efficiency and objectivity in assessing work quality, strengthen employee motivation, and support strategic decision making for human resource development. These findings can contribute to the improvement of performance appraisal systems in organizations as well as provide a basis for further research in this area.